Perlawanan Kwee Kek Beng dalam Rubrik Hindia And Holland Dan Djamblang Kotjok Pada Surat Kabar Sin Po (1923-1960) - Jihan Jauhar Nafisah; Andi Suwirta (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2021)
This article aims to describe the aspirations of the figure Kwee Kek Beng who is known as an opinion maker in the history of the press movement in Indonesia in 1923-1960. The problem that will be studied in this article is: